Analisa Penyelesaiaan Transaksi Penagihan Fintek Tanpa Adanya Jaminan - Terminanto, Ade Ananto (Kopertais Wilayah I DKI Jakarta dan Banten, 2020)
Fintech has provided fresh air in the development of the financial and technological industries today. Growing so rapidly makes Technology-Based Money Lending and Borrowing Activities a business that has positive and negative impacts. With regulations that are not yet strict, many illegal investment companies are flourishing in Indonesia. The absence of collateral is a major problem for Fintek. In collecting loans, Fintek uses all personal data of debtor customers as an effort to resolve customer obligations. On the other hand, Fintek violates the rights of debtor customers as consumers because they have used the customer's personal data in resolving debts.